Analysis of Farmers` Participation in the Participatory Technology Development (PTD) Process Vis-a- Vis Plant Protection in Vegetables at Kunnathukal Panchayath - Suthan L (Department of Agricultural Extension, College of Agriculture, 2003)
The study entitled “Analysis of farmers’ participation in the participatory technology development (PTD) process vis-à-vis plant protection in vegetables at Kunnathukal Panchayat” was undertaken to find out the role played by the vegetable farmers in the PTD process. It was also aimed to study the farmers’ socio-economic characteristics and their relationship with the participation dynamics attributes . Its aim also included to analyse the factors which motivate the vegetable farmers to voluntarily participate in the PTD process and the final aim is to delineate the PTD process and to suggest suitable strategies for the PTD process. The study was conducted in Kunnathukal panchayat of Thiruvananthapuram district. A sample of 75 farmers who were intensively cultivating vegetables by means of following farming practices developed through PTD were selected for the study. It was assured after having discussion with the agricultural officers and the presidents of the Harithasangams. Well structured and pretested interview schedule was used for data collection. The study revealed that in Kunnathukal panchayat, farmers’ role perception about PTD and their role performance in the PTD activities were found to be extremely high. Most of the farmers were willing to undertake PTD technologies and showed preference to adopt PTD concepts. This shows their high level of participation in PTD. Most of the farmers in the Kunnathukal panchayat were literates and they had high level of cosmopoliteness, self concept, risk bearing capacity, credit orientation and exposure to information sources and their leadership qualities were also found to be good. Regarding the participation dynamics attributes of farmers, they had high level of innovativeness, scientific orientation, knowledge in vegetable cultivation, self-confidence, extension orientation, exposure to mass media, market perception, social participation, economic and achievement motivation. They had also perceived more than 61 labour days in a year. Source of irrigation was the main problem in Kunnathukal Panchayat. Farmers have been facing lot of problems in their cultivation, because of the water shortage. Regarding the overall view of three villages selected for the study, Vandithadam farmers had quite more knowledge regarding PTD, followed by Karakkonam and Elluvilla farmers and their participation in PTD activities also complied with the above mentioned results. Among the constraints listed out, the time delay in giving back the price of sold produce to farmers was the major one felt by VFPCK farmers and lack of storage and processing facilities was considered to be a major constraint felt by the IVDP farmers.